Social Media Use in College-age Youth: A Comprehensive Review and a Call to Action - Holmes, Hilary; Lara, Alba E.; Brown, Gregory S. (Current Psychopharmacology, 2020)
Background: Social media is a relatively new and impactful way to connect millions of people around the world. The intersection of mental health and social media is a poorly studied, yet important area of research. Specifically, with regard to college-aged youth, social media can potentially offer an educational tool to enhance mental health awareness or augment treatment when it is used for professional purposes by mental health advocates or healthcare professionals. There is also the added risk of disinformation, cyberbullying, and privacy breaches. Objective: This review aims to assess the current state of social media use and its influence on mental health, especially in college-age youth. Methods: The authors of this paper utilized PubMed and Medline databases to review the most recent experimental studies and literature reviews available on the topic of mental health and social media. Results: Abstracts and relevant papers were read in full, and information from these studies was cited accordingly. Conclusion: The authors conclude that although more research needs to be conducted, social media may offer benefits for mental health awareness, education, and treatment, specifically in populations such as college-age youth.
Keywords: young adult